The Impact of Nationalism, Patriotism and Internationalism on Consumer Ethnocentric Tendencies - Balabanis, George; Diamantopoulos, Adamantios; Mueller, Rene Dentiste; Melewar, T.C. (Journal of international business studies, 2001)
The study investigates the impact of patriotism, nationalism and internationalism as antecedents to consumer ethnocentrism in Turkey and the Czech Republic. Controlling for demographics, the findings indicate that the impact of patriotism and nationalism is not consistent across the two countries. Consumer ethnocentrism in Turkey is fueled by patriotism, and in the Czech Republic by nationalism. Internationalism does not have a significant effect on consumer ethnocentrism in either country. Managerial implications of these findings are considered and future research directions are identified.